PEMANFAATAN CHANNEL YOUTUBE SEBAGAI MEDIA DAKWAH (STUDI PADA AKUN YOUTUBE ANZA CHANNEL K.H ANWAR ZAHID) - M. Alfaynanur Rifqi (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2024)
Technological developments are increasingly rapid and can be reached quickly by social media users. YouTube is the platform most used by users with a user percentage reaching 65.41%. Based on this phenomenon, many preachers use YouTube social media to convey their preaching messages through video content. This research aims to determine the use of K.H Anwar Zahid's Anza Channel YouTube channel as a medium for Islamic preaching. This research uses the library research method, namely with data sources obtained from main informants including viewers of this channel. The data collection technique was carried out by observing and documenting online on the Anza Channel YouTube account. The results of this research show that the use of YouTube social media is a bridge for preachers to carry out their preaching activities via YouTube. One of the times is that the Anza Channel YouTube account which contains K.H Anwar Zahid's preaching content can be easily accessed by its subscribers. In this case, da'wah is no longer limited because it can be easily reached and makes it easier for many people to access information about da'wah through the social media YouTube. The video content uploaded to the Anza channel account is packaged in an attractive way so that it gives a good impression to subscribers, especially on K.H Anwar Zahid's Anza channel account.